[3.2.1] and [4.1.1] isomers of Lehn's [2.2.2] Cryptand: Prediction of ion selectivity by quantum chemical calculations XV. Issue 8 (18th March 2021) - Ćoćić, Dušan; Manaa, Aliya; Siegl, Selina; Puchta, Ralph; van Eldik, Rudi
Abstract: Selective alkaline and earth alkaline metal ion encapsulation by two different Lehn‐type cryptands, noted as [3.2.1] and [4.1.1], was predicted and between them compared on the DFT (B3LYP/LANL2DZp) basis set. Since these cryptands are isomers to the well‐known [2.2.2] cryptand, the cation encapsulation selectivity of all three cages were compared. The ion selectivity and ability of the host to adjust their structure to successfully accommodate the metal ions, were based on energy and geometric criteria. Different lengths of O‐Et‐O‐bridging arms provide an unsymmetrical cryptand host with great flexibility to accommodate large alkali and alkaline earth metal cations. Abstract :